Beyond venue shopping and liberal constraint: a new research agenda for EU migration policies and politics. Issue 3 (4th March 2018) - Bonjour, Saskia; Ripoll Servent, Ariadna; Thielemann, Eiko
ABSTRACT: European Union (EU) asylum and immigration politics and policies have witnessed a major change since their communitarization in the early 2000s. Studies on EU migration, however, do not agree on the impact that EU institutions now have on policy outputs and outcomes. While some argue that supranational institutions are able to impose 'liberal constraints' on member states, other studies consider them unable to shift the 'policy core' of EU migration policies. Many of these disagreements stem from unspecified theoretical assumptions and very different methods to assess influence and change. This research agenda demonstrates how drawing on new institutionalism and policy analysis literature can generate new insights in three important areas of migration policy research: the dynamics of preference formation of member states and EU institutions, the relative power and influence of member states and EU institutions, and their impact on the domestic politics and policies of member states.